Can calcitonin gene‐related peptide monoclonal antibodies ameliorate writer's cramp and migraine? - Keisuke Suzuki; Shiho Suzuki; Hiroaki Fujita; Hirotaka Sakuramoto; Mukuto Shioda; Koichi Hirata (Wiley, 2024)
Abstract Recently, calcitonin gene‐related peptide (CGRP) monoclonal antibodies (mAbs) have become available as a prophylactic treatment for migraine and have shown high efficacy and safety in clinical practice. CGRP mAbs have been reported to be effective not only for migraine but also for other comorbidities, such as psychiatric complications in patients with migraine. However, there are no reports examining the effect of CGRP mAbs on dystonia. We treated a patient with comorbid migraine and focal task‐specific dystonia (writer's cramp) with a CGRP mAb (erenumab) because of an increase in monthly migraine days despite the addition of migraine prophylaxis. In this patient, erenumab treatment for 3 months led to improvements in symptoms of both focal dystonia and migraine, suggesting a role for CGRP in the pathophysiology of both conditions.